PENGARUH STRUKTUR KEPEMILIKAN MANAJERIAL DAN GROWTH OPPORTUNITY TERHADAP STRUKTUR MODAL DAN KINERJA KEUANGAN PERUSAHAAN (STUDI PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DAN KONSUMSI BARANG YANG TERDAFTAR DI BEI PERIODE 2009-2012) - Mimi Khairani; Yulia Efni; Haryetti - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study was to determine whether there is any effect of Managerial Ownership Structure and Growth Opportunity for Financial Performance Company with capital structure as an intervening variable in the manufacturing industry sector and consumption of goods listed on the BEI 2009-2012.The population in this study were 26 companies Manufacturing Industry sector and consumption goods listed on the BEI. Hypothesis testing conducted in this research is by using statistical methods, namely; normality test, linear and coefficient of determination. Based on the hypothesis testing and data analysis has been carried out in this study can be concluded regarding the influence of Managerial Ownership Structure and Growth Opportunity for Financial Performance Company with capital structure as an intervening variable.Based on the results of this study indicate that the Managerial Ownership Structure not significant effect directly on capital structure, Growth Opportunity significantly influence directly on Capital Structure, Ownership Structure Managerial no significant effect directly on the Financial Performance of the Company, Growth Opportunity no significant effect directly on the Company's Financial Performance. Capital Structure significant effect on the Company's financial performance directly, but the capital structure are not able to moderate the relationship between Managerial Ownership Structure and Corporate Financial Performance. In addition, Capital Structure able to moderate the relationship between Growth Opportunities and Corporate Financial Performance.Keywords: Managerial Ownership Structure, Growth Opportunities, Capital Structure and Corporate Financial Performance.